A commitment to hope - Jason Wolf (The Beryl Institute, 2020)
On April 1, we made the decision to reconfigure our scheduled special issue on Behavioral Health to the topic of this issue - Sustaining a Focus on Human Experience in the Face of COVID-19. In the midst of crisis, we were uncertain how people would respond to this call or even if they could in the face of the realities they were addressing each day. Yet, the research, cases and stories started to arrive. The contributions in this special issue represent a patchwork of powerful insights and a historic record to document this moment. What we have brought together includes the best of real-time insights and research, powerful stories and personal reflections that are so central to this time, one that has called on all of us to dig deeper, ask ourselves personal and essential questions and remind ourselves what really matters overall. We are deeply moved and inspired by the speed, thoughtfulness and comprehensive nature with which our contributors engaged, many of whom were tackling this crisis but still took time to contribute to a conversation beyond themselves. That may be the most powerful lesson of all: that in struggling with each of our own personal or individual organizational issues, we remained called to come together to share something beyond ourselves. As you review the pages that follow, we challenge you to uncover a new idea or practice; discover an inspiration or opportunity to reflect, release or breathe; find a seed of hope. For in the generous and both heartful and thoughtful words of our contributors, we not only capture this moment in our history, we also feed the roots of possibility from which we will all spring in the days ahead. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens